Boron Nitride Doped Polyhydroxyalkanoate/Chitosan Nanocomposite for Antibacterial and Biological Applications - Mukheem, Abdul; Shahabuddin, Syed; Akbar, Noor; Miskon, Azizi; Sarih, Norazilawati Muhamad; Sudesh, Kumar; Ahmed Khan, Naveed; Saidur, Rahman; Sridewi, Nanthini (MDPI, 2019)
The present research focused on the fabrication of biocompatible polyhydroxyalkanoate, chitosan, and hexagonal boron nitride incorporated (PHA/Ch-hBN) nanocomposites through a simple solvent casting technique. The fabricated nanocomposites were comprehensively characterized by Fourier transform infrared spectroscope (FT-IR), field emission scanning electroscope (FESEM), and elemental mapping and thermogravimetric analysis (TGA). The antibacterial activity of nanocomposites were investigated through time-kill method against multi drug resistant (MDR) microbes such as methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli (E. coli) K1 strains. In addition, nanocomposites have examined for their host cytotoxicity abilities using a Lactate dehydrogenase (LDH) assay against spontaneously immortalized human keratinocytes (HaCaT) cell lines. The results demonstrated highly significant antibacterial activity against MDR organisms and also significant cell viability as compared to the positive control. The fabricated PHA/Ch-hBN nanocomposite demonstrated effective antimicrobial and biocompatibility properties that would feasibly suit antibacterial and biomedical applications. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.